PERSPEKTIF AGAMA TENTANG KESETARAAN GENDER DI INDONESIA: ANALISIS TEOLOGIS DAN SOSIAL TERHADAP PERAN PEREMPUAN - Yanto Sandy Tjang; Herkulana Mekarryani Soeryamassoka; Victoria Julianti Siska Ubeq; Vensius Rico Novi Andry; Theresia Lina Iswaraningsih; Yosephin Metauli Situmorang (STP Reinha Larantuka, 2025)
Gender equality has become a major concern in Indonesia’s religious life, influenced by patriarchal social structures and diverse interpretations of women’s roles. This study explores the theological foundations of gender equality in six official religions: Islam, Protestantism, Catholicism, Hinduism, Buddhism, and Confucianism, and examines the gap between doctrinal ideals and socio-religious practices. Using a qualitative approach through literature review and interreligious comparative analysis, data were drawn from sacred texts, institutional documents, and academic works, analyzed through theological hermeneutics and sociological perspectives. Findings show that all religions recognize theological principles of gender equality, yet implementation is limited by patriarchal norms and historical traditions. Egalitarian values are often constrained by gender-biased structures. Inclusive theological reinterpretation is essential to align religious teachings with modern contexts and strengthen women’s participation in public and religious spheres. Achieving gender equality requires critical interfaith reflection to promote social justice and uphold human dignity.